Sex distinctive patterns in the association between serum bicarbonate and uric acid levels among healthy adults. Qatar biobank data - Ibrahim, Wisam Nabeel; Shi, Zumin; Abdallah, Atiyeh M.; Abu-Madi, Marawan Abdelhamid (Frontiers in Medicine, 2023)
Background: Uric acid is the end product of purine metabolism; a powerful plasma antioxidant but with a proinflammatory effect. When present at a high level it may predispose individuals to multiple chronic diseases such as Gout, atherosclerosis, hypertension, and renal diseases. This study aimed to evaluate the gender-specific association between serum bicarbonate and uric acid levels among healthy adults. Methodology: The study was carried out in the healthy adult population using a retrospective cross-sectional design including the data of 2989 healthy Qatari adults (36.4 ± 11.1 years) from the Qatar biobank database. The analysis included the estimation of serum uric acid and bicarbonate serum levels alongside other serological markers. The study participants were free from chronic diseases and were divided into four quartiles based on the level of serum bicarbonate. The gender-specific relation between serum bicarbonate and uric acid levels was assessed through univariate and multivariate analyses. Results: In men, low serum uric acid was significantly associated with the higher quartiles of serum bicarbonate levels after adjustment for age. The association remained significant after further adjustment for BMI, smoking, and renal function. The subgroup analysis using the restricted cubic spline method confirmed a significant dose-response association between the variation coefficients of uric acid by serum bicarbonate level in men with adjustments for age, BMI, smoking, and renal function. In women, no significant association was found between quartiles of serum bicarbonate and uric acid level following the same adjustments. However, using the restricted cubic spline method, a significant bidirectional relation was demonstrated between serum bicarbonate and the variation coefficients of uric acid that was positive for serum bicarbonate levels below 25 mEq/L and negative at higher levels. Conclusion: Serum bicarbonate levels are linearly associated with reduced serum uric acid levels among healthy adult men. This might be one of the privileges in men to protect against the complications of hyperuricemia. However, this finding demand further investigations to outline the underlying mechanisms